NOVEL WASRIPIN DAN SATINAH KARYA KUNTOWIJOYO: ANALISIS STRUKTUR DAN NILAI PENDIDIKAN KARAKTER - Retno Suprihatiningsih; Herman J Waluyo; Slamet Mulyono (Universitas Sebelas Maret, 2019)
This study aims to describe and explain: (1) The structure of Kuntowijoyo's novel Wasripin and Satinah, (2) The value of character education contained in Kuntowijoyo's Wasripin and Satinah novel, (3) Relevance of structural review and educational values character of novel Wasripin and Satinah as a literary material in high school. This form of research is descriptive qualitative research. The data sources of this research are novel and informants. Technique of taking research subject is purposive sampling. Data collection techniques used is technique read dan write dan interviews. Test the validity of data using triangulation of data sources and theory. Data analysis technique used is flow analysis technique. Based on the data analysis, the results of the research conclude as follows: (1) the structure of Wasripin and Satinah novels by Kuntowijoyo covering themes, plot, characterization and character, interrelated background and point of view (2) character education values contained in novel Wasripin and Satinah is 15, that is religious, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, love homeland, friendship / communicative, peace loving, caring environment, social care and responsibility, (3) Wasripin and Satinah novels are relevant as literary teaching materials in high school because they meet the eligibility criteria of non-text book personality aspects of the material and presentation of the material.